Analyzing Auction and Bargaining Mechanism Design in E-Procurement with Quality Verification and Risk Aversion. - Huang, H. (Institutional Knowledge at Singapore Management University, 2013)
We compare two mechanisms from the buyer’s perspective in multi-attribute supply procurement, with verifiable and unverifiable quality of the supplies and risk aversion to deviation from acceptable quality: an auction mechanism and a generalized Nash bargaining mechanism. We develop a model to represent the effects on the buyer’s dominant strategy of bargaining and auction participation. The results suggest the conditions for which bargaining is preferred over the auction mechanism alone.